2021
DOI: 10.1177/1556984520978315
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Pneumothorax Diagnosis by Surgical Residents Using Portable Ultrasound

Abstract: Objective Feasibility of diagnosis of pneumothorax using handheld ultrasound by non-radiologists shows inconsistent results. The aim of this study is to evaluate the feasibility and accuracy of portable ultrasound for immediate diagnosis of pneumothorax by general surgery residents who underwent short training. Methods Patients who presented to the emergency department of a university hospital with suspected pneumothorax between 10/2018 and 12/2019 were included in the study. Patients underwent ultrasound in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Six studies involved residents (Wilkinson et al, 2014 [48], Andersen et al, 2015 [49], Maetani et al, 2018 [50], Bar et al, 2021 [51], Acheampong et al, 2022 [52]), and two studies included both students and residents (Panoulas et al, 2013 [53]; Mai et al, 2013 [54]). The year of the study was not generally reported for residents [48][49][50][51][52][53][54]. Prior to the intervention, participants had limited experience or no experience in carrying out ultrasounds (either conventional or handheld ones).…”
Section: The Traineesmentioning
confidence: 99%
See 2 more Smart Citations
“…Six studies involved residents (Wilkinson et al, 2014 [48], Andersen et al, 2015 [49], Maetani et al, 2018 [50], Bar et al, 2021 [51], Acheampong et al, 2022 [52]), and two studies included both students and residents (Panoulas et al, 2013 [53]; Mai et al, 2013 [54]). The year of the study was not generally reported for residents [48][49][50][51][52][53][54]. Prior to the intervention, participants had limited experience or no experience in carrying out ultrasounds (either conventional or handheld ones).…”
Section: The Traineesmentioning
confidence: 99%
“…General Electric's Vscan was exclusively used in 11 studies [31][32][33][34][35][36][37][38][39]41,43,49,51,53,54]. Two studies used the Acuson P10 (Siemens, [29,54]), two used the Philips Lumify [50,52], three used the Butterfly iQ [44,45,47], and one used the Ballater Medical 3-in-1 ultrasound probe (Ballater Medical, Edinburgh, UK) [46].…”
Section: The Handheld Ultrasound Devicesmentioning
confidence: 99%
See 1 more Smart Citation